Intellectual Capital, Struktur Modal dan Good Corporate Governance terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Intervening - Veronika Maharani Lim; Eny Maryanti (Program Studi Akuntansi FPEB UPI, 2023)
This study aims to determine the effect of intellectual capital, capital structure and good corporate governance on firm value with financial performance as an invervening variable. Banking companies listed on the Indonesia Stock Exchange (IDX) are the subjects of this study for the period 2018-2020. This research method uses quantitative. All banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2020 are the population in this study, with a sampling technique using purposive sampling. The population in this study obtained data as many as 141 companies, while obtaining a sample of 72 companies. In this reseacrh, the analysis method uses SmartPLS 3 (Partial Least Square). The results of this study prove that : Intellectual Capital has a significant negative effect on firm value. Capital Structure and Good Corporate Governance do not have a significant effect on Firm Value. Intellectual Capital, Capital Structure and Good Corporate Governance have a significant positive effect on Financial Performance. Financial Performance is an invervening variable between intellectual capital and firm value. Financial Performance cannot be an intervening variable between Capital Structure and Good Corporate Governance on Company Value.